An empirical study of the technological, organisational and environmental factors influencing South African medical enterprises' propensity to adopt electronic health technologies - Mamatela, Motlatsi (My University, 2014)
Information and communication technologies can be used to deliver healthcare services and improve the healthcare system. Any electronic healthcare system whose usage results in the efficient and enhanced quality of healthcare is an eHealth system and can be beneficial for medical enterprises. Despite the advantages that eHealth systems offer, medical enterprises are often reluctant to abandon their paper-based systems and embrace eHealth solutions. Through a review of existing eHealth literature, this study identified generic technologies used within South African medical enterprises. Fourteen (14) technologies, that represent a basket of eHealth systems for supporting the business management, professional clinical informatics, patient information storage and consumer health informatics functional areas, were identified. The study then aimed to determine the state of adoption of these technologies as well as the factors influencing adoption. The technological, organisational and environmental (TOE) factors that contributed to the current state of adoption were identified through a review of existing TOE literature. A model that explores the effects of these pre-determined TOE factors on the propensity to adopt eHealth was developed and tested. A cross-sectional, quantitative study was carried out and survey data was collected from a sample of 130 medical enterprises in South Africa. Data was collected using a structured questionnaire. Correlation analysis was used to test the model’s hypotheses and hierarchical regression was used to test the overall TOE model. By using the TOE framework, the study has provided a theoretical contribution and addressed a gap in the literature into the barriers and determinants of the adoption of information and communication technologies (ICTs) in healthcare. The results of the study show that South African medical enterprises use systems that range from simple electronic fund transfer systems to more complex electronic record and clinical decision support systems. Of the 14 technologies that were identified, business information systems such as medical aid claims submission systems and electronic record systems for patient and fee related information were the most adopted while a steady, but continued increase in the adoption of clinical health information systems was observed. Specifically, the study reveals that electronic fund transfer systems are the most adopted systems while ePrescription systems are the least used. Furthermore, the study shows that in addition to the enterprises’ operating period, perceived benefits, IT infrastructure, senior clinician involvement, resource commitment and external pressure are correlated with the propensity to adopt while system complexity is a barrier to technology adoption.
Keywords: eHealth; Propensity to adopt; Technology-Organisation-Environment (TOE) framework; Healthcare business management systems; Professional clinical informatics; Patient information storage system; Consumer health informatics